Clinical profile and management of pleomorphic adenoma of head neck: our experience - Pawar, Rameshwar T.; Nitnaware, Ashok Z.; Patel, Seema V.; Rekhade, Tanvi S. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2019)
Background: Pleomorphic adenoma constitutes one of the common salivary gland tumors. Our aim is to study the clinical presentation of pleomorphic adenoma, preoperative and postoperative histopathological findings and management of tumors. Methods: A retrospective study of 43 patients was conducted at department of ENT, Government Medical College and Hospital, Nagpur between January 2017 to February 2019. Data was collected and analysed. Results: Maximum patients were of age group 40-60 years with male preponderance. Parotid being most common gland involved, 35 cases of all 43 were post-operatively confirmed to be pleomorphic adenoma. Conclusions: Pleomorphic adenoma is most commonly diagnosed in age group 40-60 years. Surgical excision is treatment of choice. Long term follow-up of the cases is warranted owing to risk of late recurrences.